La gestión de la reputación digital en la red social facebook por parte de los estudiantes universitarios del ultimo semestre. estudio de caso facultad de ccss de la utmach 2023 d1 - Almendariz Parco, Jhon Stalin; Encalada Gomez, Elvis David (Machala, 2023)
This research work analyzes the management of the digital reputation in the social network Facebook of the students of the thirteen undergraduate careers of the Faculty of Social Sciences of the Technical University of Machala during the year 2023 from the use of investigative instruments such as the qualitative content analysis, interview and survey. As a result, it is noted that students make a playful-informal use of their social networks by posting leisure and entertainment information.
Este trabajo de investigación analiza la gestión de la reputación digital en la red social Facebook de los estudiantes de las 12 carreras de pregrado de la facultad de ciencias sociales de la Universidad Técnica de Machala durante el año 2023 a partir del uso de instrumentos investigativos como el análisis cualitativo de contenido, la entrevista y la encuesta. como resultado se advierte que los estudiantes realizan un uso lúdico-informal de sus redes sociales posteando información de ocio y entretenimiento.
Keywords: REPUTACION DIGITAL; WEB 2.0; REDES SOCIALES; FACEBOOK; HUELLA DIGITAL; GESTION DIGITAL; COMA CULTURA DIGITAL